A candidate transacting modulator of fetal hemoglobin gene expression in the Arab—Indian haplotype of sickle cell anemia. Issue 11 (22nd August 2016) - Vathipadiekal, Vinod; Farrell, John J.; Wang, Shuai; Edward, Heather L.; Shappell, Heather; Al‐Rubaish, A.M.; Al‐Muhanna, Fahad; Naserullah, Z.; Alsuliman, A.; Qutub, Hatem Othman; Simkin, Irene; Farrer, Lindsay A.; et al.
Abstract : Fetal hemoglobin (HbF) levels are higher in the Arab–Indian (AI) β‐globin gene haplotype of sickle cell anemia compared with African‐origin haplotypes. To study genetic elements that effect HbF expression in the AI haplotype we completed whole genome sequencing in 14 Saudi AI haplotype sickle hemoglobin homozygotes—seven selected for low HbF (8.2% ± 1.3%) and seven selected for high HbF (23.5% ± 2.6%). An intronic single nucleotide polymorphism (SNP) in ANTXR1, an anthrax toxin receptor (chromosome 2p13), was associated with HbF. These results were replicated in two independent Saudi AI haplotype cohorts of 120 and 139 patients, but not in 76 Saudi Benin haplotype, 894 African origin haplotype and 44 AI haplotype patients of Indian origin, suggesting that this association is effective only in the Saudi AI haplotype background. ANTXR1 variants explained 10% of the HbF variability compared with 8% for BCL11A . These two genes had independent, additive effects on HbF and together explained about 15% of HbF variability in Saudi AI sickle cell anemia patients. ANTXR1 was expressed at mRNA and protein levels in erythroid progenitors derived from induced pluripotent stem cells (iPSCs) and CD34 + cells. As CD34 + cells matured and their HbF decreased ANTXR1 expression increased; as iPSCs differentiated and their HbF increased, ANTXR1 expression decreased. Along with elements in cis to the HbF genes, ANTXR1 contributes to the variation in HbF in Saudi AI haplotype sickle cell anemia and is the first gene in trans to HBB that is associated with HbF only in carriers of the Saudi AI haplotype. Am. J. Hematol. 91:1118–1122, 2016. © 2016 Wiley Periodicals, Inc.